IMPLEMENTASI THERAPEUTIC COMMUNITY (TC) PADA PROGRAM REHABILITASI SOSIAL PENYALAHGUNAAN NARKOBA DI BALAI BESAR REHABILITASI BADAN NARKOTIKA NASIONAL LIDO KABUPATEN BOGOR - Yasmin, Aulia; Supiadi, Epi; Deswanti, Arini Dwi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
This study examines the implementation of the Therapeutic Community method (TC) in the Social Rehabilitation Program for drug abusers at the National Narcotics Agency (BNN) Lido, Bogor Regency. TC prioritizes support from a positive social environment to provide positive mutual support and restore their social functioning. This study is a descriptive qualitative study. Informants in this study used a purposive sampling technique with a total of 7 informants consisting of 2 rehabilitation clients, 1 counselor, 1 nurse, 1 inpatient officer, 1 psychologist, and 1 vocational trainer at BNN Lido. The results of the study indicate that the implementation of the TC method is carried out through three stages: induction, adaptation, and facilitation. The induction stage is the stage that focuses on helping new clients become community members and involving clients in the social rehabilitation program at the rehabilitation institution. In the adaptation stage, basic life skills therapy services or vocational training are provided to develop self-abilities and work skills for clients. The facilitation stage is the development of a positive social support network. The main activities in the facilitation stage are client independence and the application of skills acquired during rehabilitation. Based on research results, the implementation of the TC method in the social rehabilitation program for drug abuse at the National Narcotics Agency (BNN) in Lido has been running according to procedure, but there is still a risk of relapse among clients after rehabilitation due to triggers from their home environment, social pressure, and lingering societal stigma. Keywords: social rehabilitation, therapeutic community, drug abuse